The influence of expertise on segmentation and memory for basketball and Overwatch videos - Newberry, Kimberly Marie (Kansas State University, 2019)
Much research has shown that experts possess superior memory in their field of expertise. This memory benefit has been proposed to be the result of various encoding mechanisms, such as chunking and differentiation. Another potential encoding mechanism that is associated with memory is event segmentation, which is the process by which individuals parse continuous information into meaningful, discrete units. Event Segmentation Theory proposes that segmentation is influenced by perceptual (e.g., motion) and conceptual (e.g. semantic knowledge) cues. Previous research has found evidence supporting the influence of knowledge on segmentation, specifically through the manipulation of goals and familiarity for everyday activities. To date, few studies have investigated the influence of expertise on segmentation, and questions about expertise, segmentation ability, and their impact on memory still remain. The goal of the current study was to investigate the influence of expertise on segmentation and memory ability for two different domains: basketball and Overwatch. Participants with high and low knowledge for basketball viewed and segmented basketball and Overwatch videos at coarse and fine grains, then completed memory tests. Differences in segmentation ability and memory were present between experts and novices, specifically for the basketball videos; however, segmentation only predicted memory for activities for which knowledge was lacking, for experts. Overall, this research suggests that experts’ superior memory is not due to their segmentation ability and contributes to a growing body of literature showing evidence supporting conceptual effects on segmentation.
Keywords: Expertise; Memory; Knowledge; Segmentation; Event Cognition